2010
DOI: 10.4049/jimmunol.0903642
|View full text |Cite
|
Sign up to set email alerts
|

Swiprosin-1/EFhd2 Controls B Cell Receptor Signaling through the Assembly of the B Cell Receptor, Syk, and Phospholipase C γ2 in Membrane Rafts

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 80 publications
2
77
0
Order By: Relevance
“…Additionally, cytokine secretion in human mast cells is thought to be guided by swip-1/EFHD2 (Ramesh et al, 2009). Hemocytes, macrophage-like cells of the invertebrate innate immune system, are known to transcribe CG10641 (Estrada et al, 2006; Kroczek et al, 2010) and our study found a polar distribution of Drosophila Swip-1 in the macrophage-like hemocytes of the embryo. Taken together, these findings suggest a conserved function of swiprosin in the innate immune system of invertebrates and vertebrates.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Additionally, cytokine secretion in human mast cells is thought to be guided by swip-1/EFHD2 (Ramesh et al, 2009). Hemocytes, macrophage-like cells of the invertebrate innate immune system, are known to transcribe CG10641 (Estrada et al, 2006; Kroczek et al, 2010) and our study found a polar distribution of Drosophila Swip-1 in the macrophage-like hemocytes of the embryo. Taken together, these findings suggest a conserved function of swiprosin in the innate immune system of invertebrates and vertebrates.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, in many aspects, the Drosophila protein is highly conserved with mammalian swiprosins (Fig. 1), and therefore, we named the CG10641 protein Drosophila Swip-1 in accordance with Kroczek and colleagues (Kroczek et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calcium flux measurements were performed as described (42,43 was restored after 240 s. Changes in Indo-1 AM fluorescence ratios were analyzed in gated FO and MZ B cell populations with a LSRII flow cytometer (BD Biosciences) using FlowJo software (Tree Star). Equal Indo-1 loading was assessed by ionomycin stimulation.…”
Section: Methodsmentioning
confidence: 99%